Increased Use Value of Coffee Bean Skin Waste as Liquid Fertilizer in Sukorambi Jember Area - Nur Faizin (LP2M Universitas Jember, 2019)
The Faculty of Engineering's community service program, University of Jember, with a partner, the Sumber Kembang Kelompok Tani (Farmer Group), aims to overcome partner problems, about the accumulation of coffee bean skin waste that is not utilized. So far, the Sumber Kembang Kelompok Tani (Farmer Group) has not utilized coffee waste properly. The waste of the coffee bean skin will be processed into liquid fertilizer. The community service team will act as a facilitator and instructor in training or mentoring, which includes: 1. Explanation of the use and method of making liquid fertilizer from coffee bean skin, 2. Training related to the use of tools and processes for making liquid fertilizer, 3. Monitoring activities after socialization and training. The results of this training and service are that farmers have the ability to make liquid organic fertilizer from coffee bean skin waste expected to increase partners' understanding in processing coffee bean skin waste into liquid fertilizer and adding economic value from coffee bean skin waste so that it has a higher selling value.